2012
DOI: 10.4028/www.scientific.net/amr.616-618.614
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pulp pH on Flotation of Fluorite and Calcite

Abstract: Pulp pH value plays a significant role in the froth flotation. Especially in the flotation of fluorite, the performance of flotation will be affected greatly by pulp pH. MO, a new kind of modified fatty acid was used as collector, and H2SO4 and Na2CO3 were used to regulate pulp pH in the experiment. The mechanism of influence of pulp pH on flotation of fluorite and calcite was investigated by such parameters as fluorite recovery, zeta potentials and the infrared spectroscopy about minerals at different pulp pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Rapid coagulation occurs at zeta potentials of 0 to +5 or -5. The range of zeta potentials for fluorite lies near pH 9.5 [25]. Hence, the high recovery of fluorspar and maximum percent reduction in gangue occurred at pH 10, as shown in Figs.…”
Section: Effect Of Phmentioning
confidence: 74%
See 2 more Smart Citations
“…Rapid coagulation occurs at zeta potentials of 0 to +5 or -5. The range of zeta potentials for fluorite lies near pH 9.5 [25]. Hence, the high recovery of fluorspar and maximum percent reduction in gangue occurred at pH 10, as shown in Figs.…”
Section: Effect Of Phmentioning
confidence: 74%
“…3 and 4 show the effects of pH on weight percentage concentration of fluorspar and percentage reduction in gangue, respectively. The results revealed the optimal feed pH to be 10 for the recovery of fluorite from fluorspar ore, which leads to a decrease in the recovery of calcite from fluorspar ore at pH > 10 [25]. In the range of pH from 7-11 has a relationship with the point of zero charge of fluorite [20].…”
Section: Effect Of Phmentioning
confidence: 95%
See 1 more Smart Citation
“…Slurry pH can directly change the surface dissolution of fluorite and calcite, thereby affecting flotation behavior. Sodium hydroxide, sodium carbonate and sulfuric acid are commonly used as pH regulators in flotation separation of fluorite and calcite [83,100].The flotation behavior of fluorite at a high pH (>12) is distinctly different from that at a conventional flotation pH range of 8-9 [35], and efficient calcite/fluorite separation could be achieved by using a low collector dosage at pH 13 (sodium hydroxide as the pH regulator).Wang et al [101]found that a green and low-cost 1-hydroxyethylidene-1,1-diphosphonicacid (HEDP) can be used as a pH-dependent switch to initially depress fluorite for calcite pre-removal at pH 6.0 and then activate fluorite for further upgrading fluorite concentrate at pH 8.0.…”
Section: Ph Regulatormentioning
confidence: 99%
“…For example, the zeta potential is affected by the pH level of the pulp and it affects the stability of the suspension [28]; if it is too low, flocculation occurs, which causes poor flotation selectivity, while if it is too high, the suspension remains stable. Some authors have analyzed, in detail, the effect of pulp pH on the flotation of fluorite and calcite [29].…”
Section: Introductionmentioning
confidence: 99%